Optimizing Biodegradation of Floating Diesel Fuel Contaminated Wastewater Using the Taguchy Method - Amir Reza Talaie; Mohammad Reza Talaie; Nematolah Jafarzadeh Haghighifar (آب و فاضلاب, 2009)
In this study, biodegradation of floating diesel fuel was investigated by using two gram negative strains designated as A1 and A2 which were isolated from a reservoir tank of a gas station in Isfahan. One of them was identified as pseudomonas aeruginosa. The percent removal of diesel fuel was evaluated for pure and mixture cultivations. The highest removal percent belomged to A1, which was able to remove 88% of the floating diesel fuel. Also the evaluation of emulsification index (E24) of the cultivation mixture indicates that the microorganisms can produce a significant amount of biosurfactant. The emulsification index values for A1 and A2 were 23% and 21%, respectively. pH, nitrogen source concentration, fuel concentration, and salinity at three levels were investigated and the optimum values of these parameters were determined at 8, 0.55 g/lit, 2%, and 8%, respectively.